Nutritional Status of School-aged Children with Intestinal Parasite Infection in South Jakarta, Indonesia - Sari, Ika Puspa; Audindra , Sacha; Zhafira, Aqila S.; Rahma, Arin A.; Syarira, Cut V.; Wahdini, Sri (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The prevalence of intestinal parasitic infection still high in Indonesia and lead to nutritional disorder, especially in the school-aged children. AIM: This research conducted to find the association of intestinal parasitic infection to the nutritional status of the children. METHODS: This was a cross sectional study, conducted in January 2016 in one primary school in South Jakarta, Jakarta, Indonesia, by collecting the children’s stool from 1st to 5th grade. Direct examination of the stool was conducted in the Parasitology Department, Faculty of Medicine, Universitas Indonesia, by Lugol and eosin staining. Nutritional status categorized using BMI chart. Data were analyzed using Chi-square test, Statistical Product, and Service Solutions version 20. RESULTS: From the total 157 stool examined in the laboratory, there were 60 (38.2%) children positively infected with various kinds of intestinal parasites. Mostly the infection is caused by Blastocystis hominis, which infects 44 children (69.4%). The other infection is caused by Giardia lamblia (15.3%), Trichuris trichiura (1.4%), and hookworm (1.4%), and mixed infection of B. hominis and Escherichia coli (4.2%) and B. hominis with G. lamblia (4.2%). From the total of infected children, 17 children (28.3%) have BMI below 5th percentile, and it was considered as malnourished. Moreover, 67 uninfected children have normal nutritional status. Statistically, there is an association between intestinal parasitic infection and nutritional status in school-aged children in South Jakarta (P < 0.05). CONCLUSION: The incidence of intestinal parasitic infection in school-aged children is 38.2%. Moreover, 28.3% of the infected children were malnourished and it is suggested that children with intestinal parasite infection have low nutritional status.